Developing a Counseling Tool for Determining the Choice of Contraceptives in Women of Fertile Age - kenik sri wahyuni (P3M Universitas 'Aisyiyah Surakarta, 2021)
In 2016, the CPR (Contraceptive Participant Rate) was 57.9%. Efforts to increase CPR are pursued by launching a family planning program, through an educational approach and introducing various contraceptives at childbearing age, the government is striving to reduce population growth very quickly (BKKBN, 2016).Research Objectives: To develop counseling aids. Research Methods Using the research action cycle, qualitative methods with 5 midwives and 5 patients.Research location in Sleman Regency, Yogyakarta.Analysis techniques using thematic analysis.Research Results: Communication patterns between providers and patients tend to be in two-way communication patterns. In the use of assistive devices, all providers do not use ABPK in the KB counseling process for various reasons. Although the impact is positive, namely the availability of a complete source of information from each contraceptive Conclusion: The development of counseling aids has changed from a manual design to a digital-based tool, which is an application installed on Android